2019
DOI: 10.5326/jaaha-ms-6783
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study on the Effects of Long-Term Use of Methylprednisolone Acetate on the Blood Work of 25 Cats

Abstract: Twenty-five cats at a private animal sanctuary received multiple nonimmunosuppressive doses of parenteral methylprednisolone acetate for at least 3 yr. Complete blood count, chemistry, and T4 results from these cats were examined to look for statistically significant changes. Results found significant changes in triglycerides, amylase, and monocytes. However, these changes remained within the reference interval. All other values showed no significant changes. These results suggest that after 3 yr of chronic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…One study evaluated long‐term effects of glucocorticoids in asthmatic cats and found adverse effects such as polyuria and polydipsia, diabetes mellitus and fungal infection in four of 34 cats 27 . A study evaluating long‐term safety (at least three years) of methylprednisolone in 25 cats detected an increase of triglycerides, amylase and monocytes, yet changes remained within the reference interval 87 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study evaluated long‐term effects of glucocorticoids in asthmatic cats and found adverse effects such as polyuria and polydipsia, diabetes mellitus and fungal infection in four of 34 cats 27 . A study evaluating long‐term safety (at least three years) of methylprednisolone in 25 cats detected an increase of triglycerides, amylase and monocytes, yet changes remained within the reference interval 87 …”
Section: Resultsmentioning
confidence: 99%
“…27 A study evaluating long-term safety (at least three years) of methylprednisolone in 25 cats detected an increase of triglycerides, amylase and monocytes, yet changes remained within the reference interval. 87 Recommendations Systemic glucocorticoids are rapid and effective in most cats with FASS (QOE 1; SOR A). Treatment with 1.4-1.5 mg/kg once daily of methylprednisolone-induced remission in 33 of 36 cats within 14 days.…”
Section: Systemic Glucocorticoidsmentioning
confidence: 99%
“…The literature describing hyperadrenocorticism in cats is scarce, with most studies describing case series or case reports (LOE 5) 251–266 . Some reports included necropsy results or the findings of CT or abdominal ultrasound imaging, but none were focused on identifying thrombosis.…”
Section: Peco Question: Hyperadrenocorticism (Cats)mentioning
confidence: 99%
“…Oral administration of tablet‐type medications, more so than liquid formulations, can be challenging in feline patients, which can decrease compliance and result in lack of disease control 13 . Parenteral glucocorticoids are commonly utilised for patients with feline HD that are difficult to medicate orally, and their use may be associated with an increased risk of acute‐onset congestive heart failure 14–17 …”
Section: Introductionmentioning
confidence: 99%
“…13 Parenteral glucocorticoids are commonly utilised for patients with feline HD that are difficult to medicate orally, and their use may be associated with an increased risk of acute-onset congestive heart failure. [14][15][16][17] At this time, there are no registered oral liquid glucocorticoids for the treatment of feline HD in the United States. Commercial compounding pharmacies offer oral glucocorticoid liquid formulations with various flavours for cats.…”
Section: Introductionmentioning
confidence: 99%